Complexos fosfínicos de Pd(II) com produtos naturais: síntese, caracterização, avaliação da citotoxicidade e interação com biomoléculas - Dutra, Jocely de Lucena (Universidade Federal de São Carlos, 2023)
This thesis details the synthesis, characterization and evaluation of antitumor activity of twelve monocationic PdII/phosphine complexes featuring ligands derived from products natural. The complexes were categorized in three Series: Series A; complexes with the general formula [Pd(cur)(P-P)]PF6, where cur=curcumin, PF6=hexafluorophosphate and P-P= PPh3=triphenylphosphine (A1), dppe=1,2-bis(diphenylphosphine)ethane (A2), dppp= 1,3-bis(diphenylphosphine)propane (A3), dppb=1,4'-bis(diphenylphosphine)butane (A4) and dppf=1,1'-bis(diphenylphosphine)ferrocene (A5); Series B, complexes with the general formula [Pd(dppe)(O-O)]PF6, where O-O= lau=lausone (B1), lap=lapachol (B2), lpm=3-styryl-lausone (B3) and ali=alizarin (B4); Series C, complexes of the type [Pd(P-P)(lap)]PF6, where P-P= dppp (C1), dppb (C2) and dppf (C3). Their characterization involves elemental analysis, molar conductivity, absorption spectroscopy in the infrared region, 1D and 2D nuclear magnetic resonance (31P{1H}, 1H and 13C{1H}), mass spectrometry and single-crystal X-ray diffraction. Stability assessment in biological relevant solvents, using UV-vis absorption spectroscopy, revealed instability on Series A, due to the self-oxidation of curcumin, as previously reported, while the Series B and C complexes were stable. The antitumor activity was evaluated in variety of cell lines, such as breast (MDA-MB-237, MCF-7 and SKBR-3), lung (A549), prostate (DU-145), ovarian (A2780 and A2780cis) and non-tumor cells of the breast (MCF-10A) and lung (MRC-5), varying the number of lines in each Series. Series A complexes showed low IC50 in several of the tumor lines tested, including some cell lines which the activity is superior to curcumin and cisplatin. The [Pd(cur)(PPh3)2]PF6 stands out in tumor lines MDA-MB-231 (5,0 ± 0,2 M), A2780 (0,5 ± 0,1 M) and A2780cis (1,4 ± 0,4 M) than the other complexes in the series, with the highest selectivity index displayed for the A2780 lineage (≥40). Series B systematically demonstrates the effects of naphthoquinones and anthraquinone coordination to Pd on IC50 values, highlighting the lapachol complex (B2) as the most active in of tumor cells tested, especially for A2780 (IC50 3.5 ± 0,1 µM, SI ≥ 11.4). In series C, C3 complex stands out presenting IC50 1.1 ± 0.2 M and SI ≥ 36.4 in A2780cis. In general, complexes A1, B2 and C3 were able to inhibit colony formation and induce morphological changes in tumor lines. Furthermore, the A1, B2, and C3 complexes promoted a cycle cell arrest in the Sub-G1 phase, which represents the fraction of dead cells with fragmented DNA. The flow cytometry assay with Annexin-V and 7-AAD showed that the complexes induce cell death by apoptosis. The complexes demonstrated weak and reversible interactions with the minor groove of DNA, without affecting its secondary and tertiary structures. Interaction assays with HSA were performed, revealing moderate to strong interactions with the complexes. The possible mechanism of death for the complexes is by inducing the formation of ROS in cells, as demonstrated for the A1 complex in A2780cis cells.
Phosphine complexes of Pd(II) with natural products: synthesis, characterization, evaluation of cytotoxicity and interaction with biomolecules
Keywords: Bioinorganic; Bioinorgânica; Palladium; Paládio; Natural products; Produtos naturais; Citotoxicidade; Cytotoxicity; Curcumin; Curcumina; CIENCIAS EXATAS E DA TERRA::QUIMICA